549 Sentinel lymph node mapping with indocyanine green in robotic-assisted laparoscopic surgery for early endometrial cancer: a population-based cohort study. (4th December 2020) - Tranoulis, Anastasios; Awad, Hebatallah; Thomson, Christina; Fisher, Amy; Twigg, Jeremy
Abstract : Introduction/Background: The sentinel lymph node (SLN) biopsy may have a key role in endometrial cancer (EC), as the therapeutic effect of lympadenectomy per se remains a field of contention. The aim of this study was to analyse our experience using indocyanine green for SLN mapping in a minimally robotic-assisted laparoscopic approach with Da Vinci Si near-infrared (NIR) fluorescence imaging system. Methodology: This is a retrospective population-based cohort study of prospectively collected data, spanning the period from January 2015 to March 2020. A total of 172 women, who underwent robot-assisted laparoscopic surgery with the Da Vinci Si Surgical System with NIR imaging and indocyanine (ICG) fluorescence detection for early stage EC, were enrolled. Cervical injection with ICG (2 ml) was performed for all patients. Baseline demographics, peri-operative and follow-up data were prospectively collected. We calculated the unilateral and bilateral detection rate. Possible correlations amongst the variables were examined using the Spearman's correlation coefficient (rho), whilst multivariate logistic regression was performed to identify independent predictors of unilateral/bilateral detection. Results: He mean age and BMI was 66.9 years and 31.8 Kg/m2, respectively. 90 women (52.3%) were diagnosed with endometrioid histology, whilst 82 with other high-risk histology. In total, 321 SLNs were removed, whilst at least one SLN was obtained in 151 women for a detection rate of 87.8%. In 106 women (61.6%) bilateral SLNs were successfully mapped. On average 1.87 (0–5) SLNs were detected per patient. SLNs were most commonly identified in the external iliac basins (78.2%), followed by the obturator fossa (10.3%), internal iliac basins (5.9%), common iliac basins (3.73%), pre-sacral (0.93%) and para-aortic region (0.93%), respectively. Lymph node metastasis was detected in 25 women (14.5%). There was no statistical correlation between the SLN detection and the age, BMI, grade and histology, respectively. The bilateral SLN detection was adversely correlated with grade 3 (rho=-0.29, p-value=0.0001 and high-risk histology (rho=-0.3, p-value=0.0001). In multivariate analysis, both grade (OR=0.21, p-value=0.005) and high-risk histology (OR=0.39, p-value=0.04) remained significant. Only three cases of Grade 1 lower extremity lymphoedema were reported. Conclusion: Intra-operative SLN mapping using fluorescence imaging with ICG in EC patients is feasible, yields high detection rates and reduces the lymphadenectomy-associated morbidity. Further studies are warranted to evaluate its accuracy in high-risk EC. Disclosures: We certify that no party has a direct interest in the results of the research and that no benefit will be conferred to us or any organisation with which we are associated.